A Endothelial cell derived extracellular vesicles mediate neutrophil deployment from the spleen following acute myocardial infarction. (May 2019) - Akbar, Naveed; Corbin, Alastair; Dawkins, Sam; Lee, Charlotte; Hogg, Eleanor; Edgar, Laurienne; Gunadasa-Rohling, Mala; Banerjee, Abhirup; Melling, Genevieve; Dragovic, Rebecca; ,; Carter, Dave; et al.
Abstract : Background: Acute myocardial infarction (AMI) induces transcriptional activation of monocytes en route to the injured myocardium, in part driven by endothelial cell derived extracellular vesicles (EC-EV), which contain proteins and microRNA (miRNA) cargo. However, neutrophils are the first immune cells to arrive at sites of injury and mediate further damage to the ischemic myocardium. Here, we describe for the first time how neutrophils are released from the spleen in AMI and show that this is driven by EC-EV signalling. Methods and results: Experimental AMI in wild-type mice caused a significant increase in peripheral blood neutrophils and a simultaneous reduction in splenic-neutrophil number (P<0.01), suggesting splenic-neutrophil deployment, which is a previously unknown neutrophil reserve in AMI. Patients have elevated peripheral blood neutrophil (1.6-fold, P<0.01) and plasma EV numbers (2.2-fold, P<0.01) at the time of AMI presentation, which significantly correlate (R=0.29, P=0.037) and suggests plasma EV-neutrophil interactions. EC-EV can alter immune cell motility from the spleen (Akbar et al, 2017). Patient plasma EV (isolated by differential ultracentrifugation, EV confirmed by protein markers TSG101, ALIX, CD9, HSP70 and morphology by transmission electron microscopy) show enrichment for EC-vascular cell adhesion molecule-1 (VCAM-1) and EC-miRNA-126-3p. AMI induces EC activation; EC activation with pro-inflammatory TNF-α models this in vitro, causing increased EC-EV release (P<0.001) and enrichment for miRNA-126-3p (P<0.01). EC-miRNA-126 is a negative regulator of EC activation and may dually control EC-EV release. CRISPR-edited-miRNA-126 knock-out EC display a pro-inflammatory phenotype, as evidenced by increased VCAM-1 (P<0.001) expression and show enhanced EC-EV release (P<0.001). To better understand the potential role of miRNA-126 on neutrophil biology we analysed miRNA-126-putative-mRNA targets and compared these to neutrophil Gene Ontology (GO) pathway terms. miRNA-126-mRNA targets are significantly over represented when compared to neutrophil GO terms for: degranulation (P<0.001), activation (P<0.001), chemotaxis (P=0.008) and migration (P=0.008). EC-EV exposure to primary human neutrophils alters inflammatory IL-6 (P<0.01) and chemokine gene expression (CCL7 (P<0.01) and CCL18 (P<0.05)), substantiating bioinformatic findings. EC-EV tail vein injected into wild-type, naive mice mobilise splenic-neutrophils to peripheral blood (P<0.001), confirming splenic neutrophil mobilisation by EC-EV. Conclusions: (I) Neutrophil deployment from the spleen is a novel finding in acute injury and interactions with (II) EC-EV may mediate their splenic liberation and (III) activation following AMI, en route to the injured myocardium. The splenic neutrophil reserve may be a novel therapeutic target in AMI to modulate the inflammatory response before recruitment of cells to sites of injury.